Haltour: millennial generation halal tourism literature media - M. Heru Sunardi; Siti Nuraeni; Musdin La Nurdin (Universitas Airlangga, 2021)
Development in the management of Indonesian Halal Tourism is felt to be increasingly important along with the entry of the Millennial Era. Based on research on the performance of several Halal Tourism Managers, the current optimization of the Halal Tourism sector is still far from the potential of Halal Tourism as it should be, so Halal Tourism Managers need to take progressive steps by implementing a digitalization system. This article aims to reveal the challenges faced by Halal Tourism in terms of Literacy and Socialization of Halal Tourism in the Millennial Era, complete with the obstacles faced. In addition, it was stated about the form of strategies for using digital literacy channels, one of which: social media to carry out more optimal Halal Tourism literacy. This research is a qualitative research, using a literature study approach. The data collected related to the research were taken from several literature sources including scientific journals, several books, and related articles published in online media. As a result, by transforming towards using digital literacy channels, the management and development program for Halal Tourism can be carried out better and at the same time be able to educate the public about Halal Tourism in Indonesia.